Customer protest: Exit, voice or negative word of mouth - Bernt Krohn Solvang (International Journal of Business Science & Applied Management (IJBSAM), 2008)
Of the three forms of protest the propensity of word of mouth (WOM) seems to be the most common, and the most exclusive form of protest seems to be exit. The propensity for voice lies in between. The costs linked to voice influence the propensity for WOM. The customers seem to do an evaluation between the three forms of protest, yet the rational picture of the customers should be moderated. Leaders should improve their treatment of the customers making complaints. The more they can treat customer complaints in an orderly and nice way the less informal negative word of mouth activity they will experience and they will reduce the exit propensity and lead the customers to the complain organisation. They should also ensure that their customers feel they get equal treatment by the staff.
Keywords: 650; voice; word of mouth; WOM; exit; satisfaction; loyalty